A243 FACTORS ASSOCIATED WITH POOR QUALITY OF LIFE IN PATIENTS WITH INFLAMMATORY BOWEL DISEASE IN CLINICAL REMISSION: A CROSS-SECTIONAL STUDY. (26th February 2020) - Nazarian, A; Bishay, K; Gholami, R; Scaffidi, M A; Khan, R; Cohen-Lyons, D; Griller, N; Satchwell, J B; Baker, J; Irvine, E J; Grover, S C
Abstract: Background: Inflammatory bowel disease (IBD) is associated with a substantial burden on quality of life (QoL). Functional gastrointestinal disorders such as irritable bowel syndrome (IBS) as well as depression and anxiety are more common in patients with IBD as compared with the general population. Although poorer QoL is correlated with IBS, depression and anxiety in individuals with IBD at times of IBD diagnosis and disease activity, it is unclear what, if any, impact these may have on overall quality of life at times of disease remission. Aims: We aimed to identify factors associated with poor QoL among Canadian patients with IBD in clinical remission. Methods: We conducted a prospective, cross-sectional study to determine whether fatigue, depression, anxiety and IBS were associated with lower QoL in patients with IBD in clinical remission. We enrolled patients at a single academic tertiary care center with inactive IBD. All eligible patients completed a series of questionnaires that included questions on demographics, disease activity, anxiety, depression, and the presence of irritable bowel syndrome (IBS) symptoms. Stool samples for fecal calprotectin (FC) were also collected to assess for subclinical inflammation. The primary outcome measure was QoL assessed by the short inflammatory bowel disease questionnaire (SIBDQ), with planned subgroup comparisons for fatigue, anxiety, depression and IBS symptoms. Results: Ninety-three patients were eligible for inclusion in this study. The median SIBDQ scores were lower in patients with anxiety (P<0.001), depression (P=0.004), IBS symptoms (P<0.001), and fatigue (P=0.018). Conclusions: In this cross-sectional study, we found that anxiety, depression, fatigue, and IBS-like symptoms were all independently associated with lower QoL among patients with inactive IBD. Importantly, subclinical inflammation as defined by a positive fecal calprotectin in the absence of clinical symptoms did not have an adverse effect on QoL. The findings of this study suggest that patients with IBD would likely benefit from screening for depression, anxiety, fatigue and IBS. Further research is warranted to determine if targeted treatment of these conditions, specifically in patients with quiescent IBD would lead to improved outcomes. Funding Agencies: None